Brincadeiras como processo de aprendizagem na educação - BARRETO, Nazilda dos Santos (2023)
The present work argues about play as a learning process in education, is an important and necessary theme in the process of learning and development of the child and has as general objective to analyze the historical aspects, learning and development of children in early childhood education through playfulness. The methodology presented was a descriptive bibliography based on surveys by authors such as: Antunes (2005), Anna and Nascimento (2011), Cardoso (2017), Cintra and Jesuino (2010) and Kishimoto (1997). topic and detail of the research. The object of study for research were games, games, songs and also theoretical arguments of authors who discuss the subject, as well as demonstrate the importance of practice as a related project on the theme, as a learning process in early childhood education. With the research it was verified the great necessity to discuss playfulness in the education of the child as one of the methodologies necessary for the teaching process, and the child learns by joking. And with this research it is hoped to contribute to the education of the children and also to encourage the educators to work with the playfulness to make that the pupil has more interest for the school education, mainly when they are leaving the familiar tie for a new conviviality.